Consumption of boutique hotel experiences as revealed by electronic word-of-mouth - Carolina Fiuza Parolin; Ricardo Boeing (Tourism & Management Studies)
Postmodern society is characterised by consumers’ hedonistic behaviours and values, in which experience consumption is a form of differentiation and social elevation. This study sought to understand consumers’ online manifestations of boutique hotel experiences and individuals’ motivations for engaging in electronic word-of-mouth. The research considered prior studies on experiential consumption, as well as publications focused on understanding postmodern individuals. Netnography was used to collect data on – and analyse – post-consumption behaviours boutique hotels. Participant observation was conducted of the online manifestations of boutique hotel consumers’ experiences. The research also included computermediated speech analysis, image analysis of virtually extracted data and discourse analysis of interviews with users identified from previous interactions and online postings. This study’s approach was based on a different perspective than that of Pine and Gilmore’s work, utilising instead the experience economy, postmodern consumer analysis and boutique hotel concepts. Observations revealed that exclusivity and privacy are central elements determining consumers’ choice and definition of boutique hotels. However, online manifestations of experiences reveal exhibitionist and paradoxical behaviours.